Comparison of long-term ankle joint function after one-stage and staged microsurgical repair of open achilles tendon defects - Jianjie Mao; Yang Xiang; Hui Chu; GenYang Jin; Guangyan Su; Chang zeng Liu; Feng Zhu (Journal of Orthopaedic Surgery and Research)
Abstract Purpose To explore the differences in long-term ankle joint function between one-stage and staged microsurgical repair of open Achilles tendon defects. Methods A retrospective analysis of the surgical treatment and follow-up data of 147 patients with open Achilles tendon defects from January 2007 to September 2023 was conducted. Patients were divided into a one-stage reconstruction group (n = 81) and a staged reconstruction group (n = 66) on the basis of whether one-stage microsurgical repair was used. In the one-stage reconstruction group, 43 patients underwent vascular anastomosed fascia lata free anterolateral thigh perforator flap transplantation for repair, and 38 patients underwent descending genicular artery free flap transplantation with the adductor magnus tendon. In the staged reconstruction group, the sural neurovascular flap was used to repair the soft tissue defect in the heel area in the first stage. In the second stage, 31 patients underwent flexor hallucis longus tendon transfer, and 35 patients underwent peroneus longus muscle tendon transfer with the lateral calcaneal artery. Observations included evaluation of the continuity and healing of the Achilles tendon via colour Doppler ultrasound 3 months postoperatively and assessment of ankle joint function 2 years postoperatively using the American Orthopedic Foot and Ankle Society ankle–hindfoot score (AOFAS) and the Achilles tendon total rupture score (ATRS). Results Three months after surgery, colour Doppler ultrasound revealed good continuity of the Achilles tendon in all patients, with slight thickening and irregular fibre orientation. Two years after surgery, the ATRS and AOFAS scores of the one-stage reconstruction group were superior to those of the staged group (P ATRS < 0.05, P AOFAS < 0.05). Among the one-stage reconstruction group, patients who underwent descending genicular artery-free flap transplantation with the adductor magnus tendon presented better performance in walking on uneven surfaces, fast stair climbing, abnormal gait, plantar flexion and dorsiflexion, and inversion and eversion than did those who underwent vascular anastomosed fascia lata free anterolateral thigh perforator flap transplantation, although there was no overall functional difference (P AOFAS = 0.792; P ATRS < 0.001). In the staged repair group, patients who underwent peroneus longus muscle tendon transfer with the lateral calcaneal artery in the second stage had better postoperative follow-up ankle joint function than did those who underwent flexor hallucis longus tendon transfer (P AOFAS < 0.001; P ATRS < 0.001). Preoperative injury classification of the heel region (P < 0.001), size of the defect area in the heel region (P AOFAS < 0.001, R AOFAS = -0.397; P ATRS < 0.001, R ATRS = -0.436), and length of the Achilles tendon defect (P AOFAS < 0.001, R AOFAS = -0.429; P ATRS < 0.001, R ATRS = -0.280) were associated with postoperative follow-up ankle joint function, whereas preoperative wound infection was not associated with postoperative follow-up ankle joint function (P AOFAS = 0.690, P ATRS = 0.759). The surgical method (OR = 49.725, 95% CI: 16.996 ~ 145.478) and the preoperative heel region defect area (OR = 0.947, 95% CI: 0.903 ~ 0.992) were found to be independent risk factors affecting the postoperative follow-up of ankle joint function in patients with open Achilles tendon defects. Conclusion The use of a one-stage microsurgical reconstruction method for open Achilles tendon defects is more conducive to Achilles tendon healing and results in a better long-term ankle joint function prognosis. The use of vascularised tendon tissue to repair Achilles tendon defects is a good choice that meets the needs of anatomically and physiologically functional reconstruction of the Achilles tendon.